Environmental risk assessment of non‐native salmonid escapes from net pens in the Chilean Patagonia. (25th July 2022) - Soto, Doris; Arismendi, Ivan; Olivos, J. Andres; Canales‐Aguirre, Cristian B.; Leon‐Muñoz, Jorge; Niklitschek, Edwin J.; Sepúlveda, Maritza; Paredes, Felipe; Gomez‐Uchida, Daniel; Soria‐Galvarro, Yuri
Abstract: Here, we review extensive information to estimate environmental risks from escaped non‐native salmonids based on the assessments of hazard, sensitivity and exposure of discrete water bodies in Chile. In 2020, the country harvested about 1 million tons salmonids from net pens located along 1500 km of highly biodiverse coastline. We base our analysis on existing scientific information and authors' expert opinions including an assessment of knowledge gaps and uncertainties. Risks of environmental impacts differed by salmon species, being lowest for Atlantic salmon due to its estimated lower survival, lower ability to feed after escaping and lower reproductive capacity in the wild compared to coho salmon and rainbow trout. Overall risks due to escapes of any of the species were highest in areas of both high farming intensity and low capacity of mitigating escapes (by wild predators and fishers) such as Aysén District. At same time, risk was higher in the most farmed areas that also presented suitable habitats to support reproduction and juvenile salmonid rearing. However, the risk estimation certainty differed among species being lowest for Atlantic salmon due to insufficient monitoring of their fate in the wild. Monitoring the fate and impacts of escaped salmonids, specially in higher risk areas is recommended to improve risk projections and to prevent and mitigate further impacts. Since Atlantic and coho salmon are not yet successful invaders in Chile, research attention is urgently needed to assess the environmental consequences of escapes of these species. The present approach can be applied to any aquaculture system given the availability of information on farmed species and receiving ecosystems.